Congenital Hypothyroidism and the Deleterious Effects on Auditory Function and Language Skills: A Narrative Review - Andrade, Caio Leônidas Oliveira; Alves, Crésio de Aragão Dantas; Ramos, Helton Estrela (Frontiers in Endocrinology, 2021)
Congenital hypothyroidism is an endocrine disease commonly found in newborns and is related to the absence or reduction of thyroid hormones, which are essential for development since intrauterine life. Children with congenital hypothyroidism can develop hearing problems as thyroid hormones are crucial for the auditory pathway's development and maturation. Sensory deprivations, especially in hearing disorders at early ages of development, can impair language skills, literacy, behavioral, cognitive, social, and psychosocial development.